DEIXIS ANALYSIS IN THE STORYBOOK â€œTHE MAGIC PORRIDGE POTâ€ BY ROSIE DICKINS - Nabila Pramesti Cahyani (ReALL - Research on Applied Linguistics and Literature, 2022)
The use of simple words is important to make children quickly understand the story in children's storybooks. Therefore, the role of pragmatics in accompanying simple words is also very useful in telling stories to children. The simple words in the storybook "The Magic Porridge Pot" by Rosie Dickins become the object of analysis in this research. Deixis's analysis in the storybook â€œThe Magic Porridge Potâ€ by Rosie Dickins is the focus of research based on the theory of Yule (1996). The method used is a qualitative method. Retrieval of data using the method of documentation. The stages of data analysis are through the stages of data collection, data reduction, data description, and conclusions. The findings of this research discuss the types of deixis and reference of deictic expressions in the storybook â€œThe Magic Porridge Potâ€ by Rosie Dickins using a deixis analysis. The conclusion of this research is that there are 29 person deixis and 6 temporal deixis, so person deixis is dominant in the storybook â€œThe Magic Porridge Potâ€ by Rosie Dickins. There are also 15 anaphoric references and 10 cataphoric references, so the anaphoric reference is dominant in the storybook â€œThe Magic Porridge Potâ€ by Rosie Dickins. Keywords: Deixis, Anaphoric, Cataphoric, Reference, Deictic Expression, Storybook